ESTRUS INDUCTION BY SUPPLEMENTATION OF MURRAYA KOENIGII IN ANESTRUS HEIFERS - SATHESHKUMAR, S; PUNNIAMURTHY, N (The Indian Journal of Animal Reproduction, 2023)
The effect of Murraya koenigii supplementation on estrus induction in anestrus heifers was studied.Twenty crossbred heifers (2-3 years) diagnosed for an estrus condition were selected for the study. The animals in the treatment group (n=10) were supplemented with 100 gms of fresh Murraya koenigii leaves daily (P/O) for 30 days. Animals in the control group (n=10) were not given any treatment. Serum calcium (Ca) and phosphorus (P) levels were estimated on the day of initiation (Day1) and completion(Day 30) of the experiment. In the treatment group, six (60%) out of ten heifers exhibited estrus withina mean of 28.0 ± 2.56 days after initiation of treatment and in the control group only one heifer (10%)exhibited estrus. There was a non-significant increase in the serum Ca and P levels and improvementin Ca:P ratio in the treatment group ( 11 . 78 ± 2.41, 6.36 ± 1.66 and 1.90: 1 respectively) when comparedwith control animals (9.32 ± 2.61, 5.84 ± 1.10 and 1.59: 1 respectively). Supplementation of Murrayakoenigii leaves ( curry leaves) at the rate of 100 gms / day daily for 30 days improved the serum Ca and P levels and resulted in induction of estrus in anestrus heifers.
Keywords: Anestrus heifers; Murraya koenigii leaves; Estrus induction